Penggunaan Klausula Proteksi Diri Bagi Notaris Dalam Akta Partij Ditinjau Dari Undang-Undang Jabatan Notaris - Misbah Imam Subari; Justicia Firdaus Kurniawan (Faculty of Law, University of Jember, Indonesia, 2023)
Notary Public is an authorized official in making an authentic deed as referred to in Article 1 number 1 of Law Number 2 of 2014 concerning Amendment to Law Number 30 of 2004 concerning Notary Position. Notarial Deed is not infrequently disputed by one of the parties or other parties because it is considered to be detrimental to its interests, so that now it is not uncommon for the Notary to be criminalized in connection with the Deed he made. This research is an Normatif jurudical research with a conceptual approach and a legislative approach. The legal material obtained in this article is then analyzed using prescriptive analytical methods. The results of the study that the use of a self-protection clause is legitimate used by the Notary, remembering that in the UUJN it does not regulate in accordance with the prohibition on using the self-protection clause. Implementation of an important self-protection clause as outlined in relation to both parties requires an identifying witness and concerns the Deed of Decision of the Meeting where the Notary is not present in person. Self protection clause can also be implemented based on Article 15 paragraph 2 letter e UUJN. KEYWORDS: Clause, Protection, Deed, Authentic.